Peran Biro Perjalanan Wisata Terhadap Pelaksanaan Study Tour Sekolah: Studi Kasus di Fama Tour - Agoes, Adrian; Putra, Naufal Pratama (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2025)
This research examines the role of Fama Tour & Travel in implementing school study tours, within the context of Indonesia's national tourism goals and the educational P5 program (Projek Penguatan Profil Pelajar Pancasila). P5 is a key initiative within the Kurikulum Merdeka aimed at shaping student character based on the values of Pancasila. Employing a qualitative methodology using observation, interviews, and documentation at Fama Tour & Travel in Bandung, the study investigates the agency's processes for developing study tour packages, consulting with schools, and executing the tours. Key findings reveal a six-step package creation process, a four-stage consultation process involving schools and their committees, and three crucial roles in implementation: conceptualising attractive events, aligning programs with school objectives (including historical and cultural learning), and keeping up with current trends. The research concludes that Fama Tour & Travel effectively manages study tours and aligns its programs with the educational aims of the schools, contributing to tourism and supporting initiatives like P5. A recommendation for Fama Tour & Travel is to reconsider itinerary scheduling to avoid overly packed days.